A Descriptive Review of Telehealth for Individuals With Autism Spectrum Disorder. Issue 2 (March 2023) - Kane, Courtney L.; DeBar, Ruth M.
Since the early 2000s, telehealth has been used to provide behavior analytic intervention to individuals with autism spectrum disorder (ASD). Evaluating evidence supporting telehealth remains valuable, especially as there has been increased accessibility since the COVID-19 pandemic. Although there is empirical support for telehealth as an effective service-delivery option, important variables (e.g., costs, implementer training) remain unknown. Despite potential roles in telehealth service-delivery models, a careful review of participant prerequisite skills, implementer characteristics (e.g., experience, education), technology variables (e.g., HIPAA compliance), and skill(s) targeted (i.e., mastered or untrained skills) have not been considered. Therefore, we aimed to extend prior telehealth literature reviews by evaluating current research across variables important for telehealth service-delivery involving individuals with ASD. We found thorough descriptions of participants and implementers, implementer training, and social validity evaluations. Limitations of telehealth literature include exclusion of teen and adult participants, limited description of prerequisite skills and evaluations of direct telehealth interventions. Future research areas were identified.